2008
DOI: 10.1179/174328408x294116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tool rotational and welding speeds on microstructural and mechanical characteristics of friction stir welded A319 cast Al alloy

Abstract: The effect of the friction stir welding (FSW) parameters on the microstructure and mechanical characteristics of A319 cast Al alloy has been investigated. Plates from the investigated alloy were welded together under different tool rotational (v) and welding (u) speeds. The results showed the possibility of welding and obtaining sound joints from A319 cast Al alloy using FSW. The welded zones exhibited many advantages over the base material (BM) such as, lower porosity content, extra fine non-dendritic a-Al gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 13 publications
3
29
0
Order By: Relevance
“…The average grain size increased proportionally to rotational speed as 5.5 mm at 450 rpm, 9.5 mm at 650 rpm and 12.8 mm at 850 rpm. Similar result that the grain size tended to increase with increasing rotational speed was also observed in many previous studies [10][11][12] and commonly with respect to the frictional heat input. Frigaard et al 13) reported that the average heat input per unit time for FSW could be described as Q ¼ 4=3 2 PR 3 !, where P was the vertical pressure on the tool, R was the surface radius of the shoulder, was the friction coefficient, and !…”
Section: Methodssupporting
confidence: 90%
“…The average grain size increased proportionally to rotational speed as 5.5 mm at 450 rpm, 9.5 mm at 650 rpm and 12.8 mm at 850 rpm. Similar result that the grain size tended to increase with increasing rotational speed was also observed in many previous studies [10][11][12] and commonly with respect to the frictional heat input. Frigaard et al 13) reported that the average heat input per unit time for FSW could be described as Q ¼ 4=3 2 PR 3 !, where P was the vertical pressure on the tool, R was the surface radius of the shoulder, was the friction coefficient, and !…”
Section: Methodssupporting
confidence: 90%
“…This means that the out flow from thread spaces forming the nugget zone in the present case differs from those identified for the case of forming onion rings [17]. Non-ring nugget structure is, however, not uncommon and can be identified in FS nuggets presented in literature for FSW/P of similar cast alloys [18][19][20][21]. RSM deposited to the nugget from thread spaces in the trailing-advancing side and the lower part (due to the screwing effect), thus forming a L-shaped RSM region in the nugget [16], as can be seen in Figure 2.…”
Section: Methodsmentioning
confidence: 49%
“…However, among these parameters, the rotation speed of the tool and welding speed are the most important that dominate the quality and mechanical properties of the joints [14,15]. To the best of our knowledge, current papers about the FSW of Al-Li alloys are few, and the conclusions in these reports about the effect of welding parameters on mechanical properties of the joints are inconsistent.…”
Section: Introductionmentioning
confidence: 69%